1985
DOI: 10.1103/physrevlett.55.829
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Scaling of the Lower-Hybrid-Current-Drive Density Limit in Tokamak Plasmas

Abstract: It is shown experimentally that the lower-hybrid current drive "density limit" is a function of the rf source frequency. While in previous 800MHz experiments this limit occurred at ie = 6 x 1012 cm-3. with a newly installed 2.45GHz, 100kW rf system on the Versator II tokamak fully rf-driven discharges have been achieved at densities up to i = 1.Ox 1013 cm-3 , without increasing the toroidal magnetic field (B < 13kG, We/W 2e > 1). Incremental current increases in ohmically heated discharges have been observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
20
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 10 publications
7
20
0
Order By: Relevance
“…Furthermore, it has been found experimentally [14] that as the frequency drops below 2ω LH , the power in the LH "pump" wave couples nonlinearly to modes that damp in the plasma edge, through a process known as the parametric decay instability (PDI) [15]. This effect adds the requirement of keeping the launched wave frequency above the parametric decay frequency 2ω LH .…”
Section: Physics Considerationsmentioning
confidence: 97%
“…Furthermore, it has been found experimentally [14] that as the frequency drops below 2ω LH , the power in the LH "pump" wave couples nonlinearly to modes that damp in the plasma edge, through a process known as the parametric decay instability (PDI) [15]. This effect adds the requirement of keeping the launched wave frequency above the parametric decay frequency 2ω LH .…”
Section: Physics Considerationsmentioning
confidence: 97%
“…al. , [19] showed that the density limit is a function of the source frequency by driving current on Versator-II with a 2.45 GHz source at densities coupling characteristics indicated that the fast wave was being launched, but the current-drive efficiency and "density limit" were identical to those of the slow wave.…”
Section: An Additional Effect Neglected In Equation 35mentioning
confidence: 99%
“…asymmetries in mirror machines, 4 as well as runaway electrons and lower-hybrid current drive ͑LHCD͒, particularly in the pioneering work of von Goeler and co-workers on the ST, 3,5 Princeton large torus ͑PLT͒, 6 and Princeton beta experiment-modification ͑PBX-M͒ 7 devices at the Princeton Plasma Physics Laboratory. The LHCD mechanism was one of the earliest 8,9 and to this day, the most efficient means of driving a noninductive electric current in a plasma, and is based on an asymmetric e.d.f. distortion in the velocity component parallel to the magnetic field, both through direct parallel momentum transfer and through the generation of an asymmetric resistivity.…”
Section: Hard-x-ray Bremsstrahlungmentioning
confidence: 99%